The Image of Poles in the Writings of Jews from the Warsaw District - Jacek Leociak (Zagłada Żydów)
This text analyzes personal documents, with emphasis laid on how certain Jews, authors of the works discussed, perceived Poles. It contains testimonies on the various aspects of Polish-Jewish relations during the occupation. In particular in focuses on: Anti-Jewish prejudice and stereotypes, the indifference of Poles toward the persecuted Jews, the actions of helpers and those aimed at offering aid to Jews, on acts of treason and violence, robbery and theft of Jewish property, as well as on acts of violence by Poles on Jews.